Novel Active-Neutral-Point-Clamped Inverters with Improved Voltage-Boosting Capability - Lee, Sze Sing; Lim, Chee Shen; Lee, Kyo Beum (IEEE Transactions on Power Electronics, 2020)
Conventional active-neutral-point-clamped (ANPC) inverters exhibit low voltage gain that inherently leads to a high dc-link voltage requirement. An improved ANPC inverter that is capable of generating five voltage levels has recently reduced the dc-link voltage twofold to achieve unity gain. This led to the development of a single-stage dc-ac power converter with no frontend boost dc-dc converter. This article proposes novel ANPC inverters capable of unity or boosted voltage gain while generating higher voltage levels. The first topology can provide a voltage gain of 1.5 and extends the number of levels to seven by incorporating only one additional switch. The topology can also be extended by adding three switches and one floating capacitor to generate nine levels with unity voltage gain, or 11 levels with a voltage gain of 2.5. The proposed ANPC inverters and their operations are comprehensively discussed. Experimental results are provided to validate the feasibility of the proposed ANPC inverters.
Keywords: 11-level inverter; Active neutral point clamped; Multi Level Inverter (MLI); nine-level inverter; Seven-level; Voltage boosting; 11-level inverter; active-neutral-point-clamped (ANPC); multilevel inverter (MLI); nine-level inverter; seven-level inverter; voltage boosting